HUBUNGAN LINGKUNGAN SEBAGAI SUMBER BELAJAR DENGAN KETERAMPILAN MENULIS PUISI PADA SISWA KELASIV - Rabuna Rabuna; Tahmid Sabri; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine whether or not there is a relationship between the environment as a source of learning and poetry writing skills in fourth grade students of SD Negeri 14 Pontianak Selatan. The research method used is a descriptive method with the form of a relationship study research using a correlation study. The population in this study amounted to 35 students and the sample used was 35 students. Data collection techniques in this study are indirect communication techniques and measurement techniques. The instrument (data collection tool) of this research is in the form of questionnaires and tests. Based on the results of statistical calculations using the product moment formula to calculate the relationship between the environment as a learning resource and poetry writing skills, rcount is 0.202. Then compared with rtable for N = 35 and a significance level of 5% of 0.334, the correlation coefficient is smaller so that rcount < rtable. Based on the results of the study, there is no relationship between the environment as a learning resource and poetry writing skills in fourth grade students of SD Negeri 14 Pontianak Selatan and is included in the low category.Keywords: Environment as Learning Resources, Poetry Writing Skills, Relationships